An Efficient Synthesis of 2-Aminothiophenes via the Gewald Reaction Catalyzed by an N-Methylpiperazine-Functionalized Polyacrylonitrile Fiber - Ma, Lichao; Yuan, Liwei; Xu, Changzhu; Li, Guowei; Tao, Minli; Zhang, Wenqin (Synthesis, 2013)
A new N-methylpiperazine-functionalized polyacrylonitrile fiber has been developed to catalyze the Gewald reaction between 2,5-dihydroxy-1,4-dithiane and activated nitriles to afford 3-substituted 2-aminothiophenes in good to excellent yields (65–91%). Low catalyst loading (8.0 mol%), simple procedure, high yields, excellent recyclability, and reusability (up to 10 times with minimal loss of catalytic activity) are attractive features of this fiber catalyst.
Keywords: Gewald reaction; 2-aminothiophene; N-methylpiperazine; polyacrylonitrile fiber; fiber catalyst